Effect of Surface-Treated Calcium-Copper-Titanate as a Lubricant Additive in Cottonseed Oil on Tribo Performance in Sliding Contacts - Gupta R.N.; Harsha A.P.; Pratap T. (My University, 2025)
The present work exhibits the tribological study of environment benign cottonseed oil, with and without blending of nanoparticles as a lubricant additive, using four-ball test rig. The present investigation focused on the close contact sliding conditions, because of the major possibilities of material loss between the dynamically mating surfaces. Surface-treated calcium-copper-titanate, CaCu3Ti4O12 (CCTO, ˂90 nm) nanoparticles, as an additive, in different concentrations (i.e. from 0.1 to 1.0%w/v) have been used in the base cottonseed oil to formulate the nanolubricant. CCTO nanoparticles have been treated with sodium dodecyl sulfate to alter the surface characteristics of the nanoadditive and form S-CCTO, to avoid nanoparticle agglomeration. The nanoparticle’s dose was optimized on the basis of minimum wear scar diameter (WSD) in antiwear test. The test nanolubricants were prepared by vigorous stirring and ultrasonication for stable and uniform suspension of the nanoparticles in cottonseed oil. The weld load property of the nanolubricants has been tested by extreme pressure property test (ASTM D2783). Worn surfaces have been characterized by using scanning electron microscope for analyzing the wear scar morphology, while for surface roughness studies, atomic force microscope has been used. The obtained test result shows that the small additive concentration improves the tribological properties significantly. It was observed that 0.25%w/v concentration exhibits maximum reduction in the WSD (i.e. 34.4%) in antiwear test, whereas in extreme pressure test, the maximum weld load was observed at 1.0%w/v. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.